Probability I. Discrete Distribution study aid - Kitaeva, A. V. economist Associate Professor of Tomsk Polytechnic University, Candidate of physical and mathematical sciences 1957- (TPU Publishing House, 2011)
This text is designed for an introductory discrete probability course at the technical university level for undergraduates in mathematics, physical and social sciences, engineering, and computer science. It presents a thorough treatment of ideas and techniques necessary for a firm understanding of the subject. The key aim has been to develop the ability to construct and analyze probabilistic models in a manner that combines intuitive understanding and mathematical precision. Complete and self-contained can be used for self-study.